Konservasi Bahasa Bali pada Kegiatan Kesubakan di Desa Mambal - Mirsa Umiyati (Warmadewa Press, 2021)
Over time, the use of regional languages ​​has changed significantly in its use. Given the ever-evolving times, changing mindsets and lifestyles that demand differences from the previous era. Currently the use of mother tongue or Indonesian and English is more desirable in its application due to the demands of an increasingly advanced era. With this phenomenon, the use of regional languages ​​is slowly becoming less attractive, especially the younger generation. To prevent this from happening, a solution is needed, namely by providing teaching or socialization in the form of conservation and revitalization of local languages. The community service program organized by Warmadewa University which aims to educate and increase the interest of the younger generation regarding the preservation of the Balinese language in cultural activities, this also has a relationship with aspects of culture and language. This activity is carried out using a descriptive qualitative method that describes real phenomena that occur in a society. The result of this dedication is that the younger generation shows an interest in fertility activities in order to continue one of the hereditary cultures that has been recognized by the world, namely Subak.